Penguatan Kompetensi Penyiaran Mahasiswa melalui Pelatihan Berbasis Praktik di Radio Telstar 102.7 FM - Lely Novia; Nurdin Noni; Sukardi Weda; Yunitari Mustikawati; Asriati (Fakultas Tarbiyah dan Ilmu Keguruan UIN Syekh Wasil Kediri, 2026)
Radio remains an important communication medium in the digital era; however, practice-based broadcasting skills among students are still limited due to a lack of direct field experience. This community service activity aims to improve students’ understanding and skills in radio broadcasting through a practice-based training approach. The method applied is experiential learning, which includes classroom theoretical briefing, a visit to Radio Telstar 102.7 FM, limited on-air practice, and follow-up classroom training for reinforcement. The results indicate an improvement in participants’ understanding of radio production processes, communicative delivery skills, as well as awareness of journalistic ethics and digital media utilization. In addition, participants demonstrated increased confidence and active participation in communication practices. This activity provides contextual learning through the integration of theory and practice, although it is limited by time constraints and the scope of practical involvement. Therefore, practice-based training shows strong potential for further development in enhancing students’ competencies in broadcasting